(untitled) (Research, Society and Development, 2021)
Objective: to evaluate The Quality of Life (QOL) of residents of an Integrated Multiprofessional Health Program in a hospital university from Recife / PE, during the COVID-19 pandemic. Methodology: This is a descriptive, cross-sectional and quantitative study, carried out with 36 residents in the areas of Nephrology and Women’s Health, in the first and second years of specialization. Data collection was carried out between August and September 2020, using as instruments a structured questionnaire to characterize participants with sociodemographic, economic, clinical and work data in the multiprofessional residency program, and SF-36, available online. For data analysis, descriptive statistics were calculated by frequency distribution and application of tests in SPSS software, version 21, considering the significance of 5%. Results: Residents had better QOL in the domains: Functional Capacity, Pain and General Health; and worse QOL in: Emotional, Vitality and Mental health. Among the participating categories,physical therapists obtained better QOL scores in all domains evaluated, except for Emotional which the psychologists stood out. When comparing the year of specialization, no results were significant between the domains, since among the area of ​​concentration, Nephrology residents obtained better results in Functional Capacity and Vitality. Conclusion: Concludes that COVID-19 was one of the markers for changes in the health status, well-being and satisfaction related to the work of multiprofessional residents in health, with a decrease in the quality of life index, according to the SF-36 domains.